Volume 8: Ocean Renewable Energy 2013
DOI: 10.1115/omae2013-10817
|View full text |Cite
|
Sign up to set email alerts
|

Summary of Conclusions and Recommendations Drawn From the DeepCwind Scaled Floating Offshore Wind System Test Campaign

Abstract: The DeepCwind consortium is a group of universities, national labs, and companies funded under a research initiative by the U.S. Department of Energy (DOE) to support the research and development of floating offshore wind power. The two main objectives of the project are to better understand the complex dynamic behavior of floating offshore wind systems and to create experimental data for use in validating the tools used in modeling these systems. In support of these objectives, the DeepCwind consortium conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
66
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 11 publications
7
66
0
1
Order By: Relevance
“…Therefore, it is recognized that some aspects of the wake may differ from that of full-scale as sway and heave are not considered. Furthermore, in studies capturing the structural response of floating bodies to wave excitations as in offshore structures, the Froude number is taken into consideration [34]. In this study, given that the movement of the mast is restricted to pitch, Froude number is not considered.…”
Section: Model Wind Turbinementioning
confidence: 99%
“…Therefore, it is recognized that some aspects of the wake may differ from that of full-scale as sway and heave are not considered. Furthermore, in studies capturing the structural response of floating bodies to wave excitations as in offshore structures, the Froude number is taken into consideration [34]. In this study, given that the movement of the mast is restricted to pitch, Froude number is not considered.…”
Section: Model Wind Turbinementioning
confidence: 99%
“…The concept has been used in previous research and it has been tested at MARIN in Wageningen (Netherlands) by the DeepCwind consortium in 2011, see Jain et al (2012), Coulling et al (2013) and Robertson et al (2013). The same model has been tested again at MARIN in 2013 with detailed analyses of the secondorder wave excitation forces and the aerodynamics at low Reynolds numbers, see Kimball et al (2014), Ridder et al (2014), Make et al (2015), Gueydon et al (2014), Gueydon (2015), Gueydon et al (2015), and Gueydon (2016).…”
Section: Introductionmentioning
confidence: 99%
“…Even though several verification test for the simulation tools have been done e.g. Robertson et al (2013), Huijs et al (2014), the simulation of the coupled floating wind turbine is still a part of current research projects. The research which is reported in Deliverable D4.2.4 of the INNWIND.EU project (Lemmer et al, 2014) focuses on the verification and validation of design methods for floating structures.…”
Section: Introductionmentioning
confidence: 99%
“…The scale of the model is 1 : 50. The model is scaled following Froude scaling laws, which are commonly used for scaling for offshore structures [48,49]. The floating hexagonal platform of the TLP is connected with six mooring tethers (ties), one at each corner of the platform, to the large circular anchoring gravity base which sits on the bottom of the wave basin during testing.…”
Section: Experimentation (A) Tension-leg Platform Modelmentioning
confidence: 99%